2020
DOI: 10.1186/s12885-020-07090-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a precision medicine pipeline to identify personalized treatments for colorectal cancer

Abstract: Background: Metastatic colorectal cancer (CRC) continues to be a major health problem, and current treatments are primarily for disease control and palliation of symptoms. In this study, we developed a precision medicine strategy to discover novel therapeutics for patients with CRC. Methods: Six matched low-passage cell lines and patient-derived xenografts (PDX) were established from CRC patients undergoing resection of their cancer. High-throughput drug screens using a 119 FDA-approved oncology drug library w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
(42 reference statements)
0
17
0
Order By: Relevance
“…The authors found a similar response to standard-of-care agents in the matched cell lines and PDX, allowing rapid analysis of sensitivity and resistance to standard-of-care agents. Moreover, from drug screening data, ponatinib, a multi-kinase inhibitor targeting several factors, including FGFR, platelet-derived growth factor receptor, vascular endothelial growth factor receptor, proto-oncogene tyrosine-protein kinases Src and Abl, was identified as a potentially effective therapeutic target for CRC for its action in inhibiting cell growth [ 105 ]. PDX model allows investigating the efficacy of the controversial anti-tumor agent.…”
Section: Patient-derived Modelsmentioning
confidence: 99%
“…The authors found a similar response to standard-of-care agents in the matched cell lines and PDX, allowing rapid analysis of sensitivity and resistance to standard-of-care agents. Moreover, from drug screening data, ponatinib, a multi-kinase inhibitor targeting several factors, including FGFR, platelet-derived growth factor receptor, vascular endothelial growth factor receptor, proto-oncogene tyrosine-protein kinases Src and Abl, was identified as a potentially effective therapeutic target for CRC for its action in inhibiting cell growth [ 105 ]. PDX model allows investigating the efficacy of the controversial anti-tumor agent.…”
Section: Patient-derived Modelsmentioning
confidence: 99%
“…Indeed, personalized medicine approaches for CRC that build on multiple ‘omics’ data and the use of patient-obtained biopsies are a promising way forward [ 215 , 216 ]. As a major step forward, recently a personalized medicine pipeline was developed, where patient-matched cell lines were used to identify new therapies and pathways to treat metastatic CRC [ 217 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput drug screening. High-throughput screens were performed in collaboration with the Duke Functional Genomics Shared Resource as previously described [34][35][36][37]. Briefly, compounds from the Bioactives library (SelleckChem) were stamped in triplicate into 384-well plates at a final concentration of 1 μM using an Echo Acoustic Dispenser (Labcyte, Indianapolis, IN, USA).…”
Section: Methodsmentioning
confidence: 99%